Short Report: Barriers and facilitators to parents' implementation of a transdiagnostic eHealth sleep intervention for children with neurodevelopmental disorders - Jemcov, Anastasija; Rosenberg, Lindsay; Tan-MacNeill, Kim; Smith, Isabel M.; Weiss, Shelly K.; Corkum, Penny (Frontiers in Sleep, 2023)
Background: Insomnia is highly prevalent in children diagnosed with neurodevelopmental disorders (NDDs) and has negative effects on physical and mental health and wellbeing. Lack of evidence-based intervention programs and barriers to treatment (e.g., time/cost) reduce treatment access. To address these problems, the possibility was explored of modifying the Better Nights, Better Days intervention for typically developing children (BNBD-TD) to make it appropriate for children with NDD. Aims: The current study’s aim was to examine qualitative data from exit interviews conducted during a usability study. Parents of children with NDD used BNBD-TD and reported on barriers and facilitators experienced while implementing the intervention. Methods/procedures: Participants were 15 Canadian parents of children aged 4 to 10 years who were formally diagnosed with an NDD. Parents implemented the BNBD-TD intervention with their children and participated in a semi-structured exit interview to provide perspectives on their user experience. Results: Based on an inductive thematic analysis, key facilitators included increased self-efficacy, positive outcomes for the family (e.g., improved sleep problems, parent validation), improved sleep related beliefs/attitudes, and increased motivation. Key barriers included time challenges, struggles when trying to improve sleep problems, and psychosocial factors with negative effects on implementation (e.g., burnout, stress, and/or exhaustion). Conclusions/implications: Barriers and facilitators identified resulted in recommendations to include more program supports, including helping parents to plan for implementation success.